Early Mobilization is Better? Comparison of isolated Non-Displaced Medial Malleolus Fracture treated with pop Cast Versus Malleolar Screw Fixation - Ali Raza, Muneeb Ur Rehman Niazi, Abdulqadir, Riaz Qadeer Niazi, Fahad Wali Shah Khaggah, Syed Hyder Raza (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Medial malleolar fractures are among the most commonly encountered injuries in clinical practice. Plaster of Paris casting is commonly used for undisplaced fractures, while multiple surgical fixation techniques for closed reduction have been described, including Kirschner wires, cancellous screws, tension band wiring, and their modifications. Objective: The objective of this study is to compare POP cast versus Single screw fixation for medial malleolus fracture of the foot. Materials and Methods: This single-blinded randomized controlled trial was conducted at the Department of Orthopedic Surgery, King Edward Medical University, Mayo Hospital Lahore, from October 2022, to April 2023. Using a non-probability consecutive sampling technique, 314 patients aged 15–60 years with closed, isolated medial malleolus fractures were enrolled, while patients with open or pathological fractures were excluded. Participants were randomly allocated into two groups using a lottery method. Group I was managed conservatively with fracture reduction followed by Plaster of Paris cast application, while Group II underwent percutaneous malleolar screw fixation. Fracture reduction in both groups was confirmed using an image intensifier. Functional outcome was assessed at the 16th postoperative week according to the operational definition of the study. Results: The mean age was 36.82 ± 13.65 years in Group A (POP cast) and 36.72 ± 14.11 years in Group B (screw fixation), with a range of 15–60 years in both groups. Group A comprised 30 males (63.82%) and 17 females (36.17%), while Group B included 26 males (55.31%) and 21 females (44.68%). Good to excellent outcomes were observed in 36 cases (76.59%) in Group A and 41 cases (87.23%) in Group B, whereas 10 (21%) and 6 (12.76%) cases, respectively, did not achieve good to excellent outcomes. Group B demonstrated a statistically significant difference in the functional outcomes compared to Group A (p < 0.05). Conclusion: Malleolar screw fixation showed statistically significant difference in functional outcomes in patients with medial malleolus fractures of the lower limbs. This technique may be considered to enhance functional recovery and reduce the risk of severe impairment. Keywords: Foot fracture, medial malleolus fractures, malleolar screw fixation, functional outcome, Olerud and Molander